2005
DOI: 10.1134/1.1922532
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of magnetic field measurements for T Tau

Abstract: It is shown that the existence of hot accretion spots at the surface of T Tau practically has no effect on the accuracy of estimation of its magnetic field strength at photospheric level.We also found that one can interpret results of T Tau's photospheric magnetic field strength measurements carried out via different methods in the frame of the following alternative: 1) if T Tau's inclination angle i ≤ 10 • , then magnetic field of the star may be dipolar with the angle between rotational and magnetic axes is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Observations suggest a non-dipolar magnetic field near the stellar surface (see Sect. 2, and also, e.g., Safier, 1998;Kravtsova and Lamzin, 2003;Lamzin, 2003;Smirnov et al, 2005). If the dipole component dominates on the large scale, many properties of magnetospheric accretion will be similar to those described above, including the structure of the funnel streams and their physical properties.…”
Section: Numerical Simulations Of Magneto-spheric Accretionmentioning
confidence: 87%
“…Observations suggest a non-dipolar magnetic field near the stellar surface (see Sect. 2, and also, e.g., Safier, 1998;Kravtsova and Lamzin, 2003;Lamzin, 2003;Smirnov et al, 2005). If the dipole component dominates on the large scale, many properties of magnetospheric accretion will be similar to those described above, including the structure of the funnel streams and their physical properties.…”
Section: Numerical Simulations Of Magneto-spheric Accretionmentioning
confidence: 87%
“…For example, a dipole with a 3 kG polar field strength (as suggested for BP Tau by Symington et al 2005) observed at an angle of 45 • would produce a net field of 690 G, well above current detection limits. Accretion hot spots are expected to have essentially no effect on net field measurements from spectropolarimetry (Smirnov et al 2005) since the acretion filling factors are typically ∼ 1% (Valenti et al 1993.…”
Section: Discussionmentioning
confidence: 99%
“…Strong polarization signals in He I 5876 Å and other accretion related emission lines have now been reported on a number of accreting T Tauri stars [50,52,54,57,235,243,251,252,265]. However, polarization measurements made using magnetically sensitive photospheric absorption lines, which presumably form uniformly across the entire stellar surface, yield small longitudinal field strengths, well below the average fields obtained from Zeeman broadening measurements [42,[234][235][236]. Commonly the net polarization signal is zero [252].…”
Section: Accreting T Tauri Stars and Observations Of Their Magnetic F...mentioning
confidence: 99%